Rainfed agriculture : unlocking the potential (Comprehensive assessment of water management in agriculture series, 2009)
This book, which contains 14 chapters, covers all aspects of rainfed agriculture, starting with its potential, current status, rainwater harvesting and supplementary irrigation, to policies, approaches, institutions for upscaling, and impacts of integrated water management programmes in rainfed areas.